2007
DOI: 10.1016/j.febslet.2007.07.036
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana trehalase is a plasma membrane‐bound enzyme with extracellular activity

Abstract: The lack of trehalose accumulation in most plant species has been partly attributed to the presence of an active trehalase. Although trehalose synthesis enzymes are thought to be cytosolic, and previous studies have indicated that trehalase activity is extracellular, the exact location of the enzyme has not yet been established in plant cell. We present evidence that the yet uncharacterised full-length Arabidopsis trehalase is a plasma membrane-bound protein, probably anchored to the membrane through a predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 31 publications
2
34
1
Order By: Relevance
“…1A). The absence of the AtTRE1 protein in wild-type rosettes is in conflict with previous immunoblots showing a faint signal of AtTRE1 in rosette leaves of bolted wild-type plants (Frison et al, 2007). The antibody used in that work was raised against two peptides of the AtTRE1 protein (residues 93-107 and 377-392), while our antibody was raised against one peptide (residues 94-107).…”
Section: Isolation and Characterization Of Arabidopsis Plants With Alcontrasting
confidence: 50%
See 4 more Smart Citations
“…1A). The absence of the AtTRE1 protein in wild-type rosettes is in conflict with previous immunoblots showing a faint signal of AtTRE1 in rosette leaves of bolted wild-type plants (Frison et al, 2007). The antibody used in that work was raised against two peptides of the AtTRE1 protein (residues 93-107 and 377-392), while our antibody was raised against one peptide (residues 94-107).…”
Section: Isolation and Characterization Of Arabidopsis Plants With Alcontrasting
confidence: 50%
“…The protein is known to contain potential N-glycosylation sites, indicating that the enzyme might be secreted (Frison et al, 2007). GFP studies confirmed that AtTRE1 is an apoplastic enzyme anchored to the cell membrane through a putative N-terminal transmembrane span (residues 46-63; Frison et al, 2007). This finding suggests that endogenous trehalose has to be transported out of the cell in order to be degraded.…”
supporting
confidence: 48%
See 3 more Smart Citations